Determination of carotenoids in sweet potato (Ipomoea batatas L., Lam) tubers: Implications for accurate provitamin A determination in staple sturdy tuber crops. (November 2019) - Drapal, Margit; Fraser, Paul D.
Abstract: Vitamin A deficiency (VAD) is a global health problem, which despite significant financial investments and initiatives has not been eradicated. Biofortification of staple crops with β-carotene (provitamin A) in Low Medium Income Countries (LMICs) is the approach advocated and adopted by the WHO and HarvestPlus programme. The accurate determination of β-carotene is key to the assessment of outputs from these activities. In the present study, HPLC-PDA analysis displayed superior resolving power, separating and identifying 23 carotenoids in the orange sweet potato ( Ipomoea batatas ) variety used, including only eight carotenoids with provitamin A properties. Additionally, the results evidently displayed that the use of lyophilised material facilitated the extraction of twice the amount of pigments compared to fresh material, which impacts the precise calculation of the provitamin A content. These results highlight that yellow to orange starchy edible crops produce a wide array of carotenoids in addition to β-carotene. Biosynthetically it is clear from the intermediates and products accumulating that the β-branch of the carotenoid pathway persists in sweet potato tuber material. Collectively, the data also have implications with respect to the determination and biosynthesis of provitamin A among staple crops for developing countries. Graphical abstract: Image 1 Highlights: β-carotene quantification by LC is far more accurate than by spectrophotometer. 23 different carotenoids are detected by HPLC in orange sweet potato. Only 9 of 23 carotenoids have provitamin A activity. Sweet potatoes express a wide range of carotenoid epoxides/furanoids.